Global Norms with a Local Face : Rule-of-Law Promotion and Norm Translation. - Zimmermann, Lisbeth (Cambridge University Press, 2017)
This book argues that global rule-of-law standards in post-conflict states are reshaped in interactive translation processes between external and domestic actors.
Keywords: Convention on the Rights of the Child.; Convention on the Rights of the Child; Rule of law.; International law.; Children's rights.; Freedom of information.; Rule of law -- Guatemala.; Règle de droit.; Enfants -- Droits.; Liberté d'information.; Règle de droit -- Guatemala.; LAW -- Essays.; LAW -- General Practice.; LAW -- Jurisprudence.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; LAW -- Reference.; Children's rights; Freedom of information; International law; Rule of law; Guatemala